Hot flow anomaly observed at Jupiter's bow shock. Issue 16 (18th August 2017) - Valek, P. W.; Thomsen, M. F.; Allegrini, F.; Bagenal, F.; Bolton, S.; Connerney, J.; Ebert, R. W.; Gladstone, R.; Kurth, W. S.; Levin, S.; Louarn, P.; Mauk, B.; et al.
Abstract: A Hot Flow Anomaly (HFA) is created when an interplanetary current sheet interacts with a planetary bow shock. Previous studies have reported observing HFAs at Earth, Mercury, Venus, Mars, and Saturn. During Juno's approach to Jupiter, a number of its instruments operated in the solar wind. Prior to crossing into Jupiter's magnetosphere, Juno observed an HFA at Jupiter for the first time. This Jovian HFA shares most of the characteristics of HFAs seen at other planets. The notable exception is that the Jovian HFA is significantly larger than any HFA seen before. With an apparent size greater than 2 × 10 6  km the Jovian HFA is orders of magnitude larger than those seen at the other planets. By comparing the size of the HFAs at the other planets with the Jovian HFA, we conclude that HFAs size scales with the size of planetary bow shocks that the interplanetary current sheet interacts with. Key Points: Observations from Juno of the first Hot Flow Anomaly detected at Jupiter's bow shock Size of Jovian Hot Flow Anomaly is orders of magnitude larger than those seen at other planets Size of Hot Flow Anomalies scale with the size of the bow shock of the planet